Leisure Tourism in Bhedetar - Koirala, Kaushal (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
This paper analyzes leisure tourism in Bhedetar, eastern Nepal. Leisure tourists usually enjoy beauty, nice hotels and resorts, and the atmosphere of natural and cultural heritage. The most popular activities of leisure tourism include social tours, cultural tours, religious tours, family tours, recreational tours, sports tours, and medical tours. Bhedetar lies at the confluence of two different geographical environments: the hills and Tarai. The geographical situation of Bhedetar plays an important role in the development of tourist destinations. Its exquisite scenic beauty, natural environment, and cultural heritage provide a reliable source of pleasure and refreshment for leisure tourists. This paper is based on both primary and secondary data sources. Primary data were collected from field observation, interaction with local people, hotel service providers, and tourists using checklists, questionnaires, and personal interviews. Secondary data were collected from books, journals, and e-resources. Tables, charts, and diagrams are used for data analysis. The findings revealed that the increasing number of hotels and lodges at Bhedetar indicated an internal market for leisure tourism. However, there are a lot of hurdles and barriers hindering the promotion of leisure tourism in this area. This paper suggests that the tourism promotion authorities should initiate action to address these barriers for the development of Bhedetar as a chosen leisure tourist destination.